Beyond thrombosis: Anti-β2GPI domain 1 antibodies identify late pregnancy morbidity in anti-phospholipid syndrome. (June 2018) - Chighizola, Cecilia Beatrice; Pregnolato, Francesca; Andreoli, Laura; Bodio, Caterina; Cesana, Laura; Comerio, Chiara; Gerosa, Maria; Grossi, Claudia; Kumar, Rajesh; Lazzaroni, Maria Grazia; Mahler, Michael; Mattia, Elena; et al.
Abstract: Antibodies against β2 glycoprotein I (anti-β2GPI) have been identified as the main pathogenic autoantibody subset in anti-phospholipid syndrome (APS); the most relevant epitope is a cryptic and conformation-dependent structure on β2GPI domain (D) 1. Anti-β2GPI domain profiling has been investigated in thrombotic APS, leading to the identification of antibodies targeting D1 as the main subpopulation. In contrast, scarce attention has been paid to obstetric APS, hence this study aimed at characterizing the domain reactivity with regards to pregnancy morbidity (PM). To this end, 135 women with persistently positive, medium/high titre anti-β2GPI IgG, without any associated systemic autoimmune diseases and at least one previous pregnancy were included: 27 asymptomatic carriers; 53 women with obstetric APS; 20 women with thrombotic APS; and 35 women with both thrombotic and obstetric complications. Anti-D1 and anti-D4/5 antibodies were tested using a chemiluminescent immunoassay and a research ELISA assay, respectively (QUANTA Flash ® β2GPI Domain 1 IgG and QUANTA Lite ® β2GPI D4/5 IgG, Inova Diagnostics). Positivity for anti-D1 antibodies, but not anti-D4/5 antibodies, was differently distributed across the 4 subgroups of patients (p < 0.0001) and significantly correlated with thrombosis (χ2 = 17.28, p < 0.0001) and PM (χ2 = 4.28, p = 0.039). Patients with triple positivity for anti-phospholipid antibodies displayed higher anti-D1 titres and lower anti-D4/5 titres compared to women with one or two positive tests (p < 0.0001 and p = 0.005, respectively). Reactivity against D1 was identified as a predictor for PM (OR 2.4, 95% confidence interval [CI] 1.2–5.0, p = 0.017); in particular, anti-D1 antibodies were predictive of late PM, conveying an odds ratio of 7.3 (95% CI 2.1–25.5, p = 0.022). Positivity for anti-D1 antibodies was not associated with early pregnancy loss. Anti-D4/5 antibodies were not associated with clinical APS manifestations. As a whole, our data suggest that anti-D1 antibodies are significantly associated not only with thrombosis, but also with late PM, while positive anti-D4/5 antibodies are not predictive of thrombosis or PM. Highlights: Positivity for antibodies against β2GPI D1 is predictive of late pregnancy morbidity. Positivity for anti-D1 antibodies is not associated with early pregnancy loss. Anti-D4/5 antibodies are not associated with clinical APS manifestations.